2008
DOI: 10.1002/pmic.200700845
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the pH response in the fungal pathogen Candida glabrata

Abstract: Micro-organisms must adapt to environmental change to survive, and this is particularly true for fungal pathogens such as Candida glabrata. C. glabrata is found both in the environment and in diverse niches in its human host. The ambient pH of these niches varies considerably, and therefore we have examined the response of C. glabrata to changes in ambient pH using a proteomic approach. Proteins expressed in C. glabrata cells growing at pH 4.0, 7.4 or 8.0 were compared by 2-DE, and 174 spots displaying reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
2
33
0
3
Order By: Relevance
“…Many studies in vitro have reported the use of a multitude of media, substrates and techniques to study biofilms (Biswas & Chaffin, 2005;Schmidt et al, 2008;Uppuluri et al, 2009). Here, we compared the effect of two commonly used media, namely RPMI 1640 and YNB, at two different pH values (pH 5.6 and 7.0) on C. glabrata and C. albicans adhesion and mature biofilm development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies in vitro have reported the use of a multitude of media, substrates and techniques to study biofilms (Biswas & Chaffin, 2005;Schmidt et al, 2008;Uppuluri et al, 2009). Here, we compared the effect of two commonly used media, namely RPMI 1640 and YNB, at two different pH values (pH 5.6 and 7.0) on C. glabrata and C. albicans adhesion and mature biofilm development.…”
Section: Resultsmentioning
confidence: 99%
“…We also elucidated the effect of pH 5.6 and 7.0 during biofilm development, because adaptation to changes in pH during biofilm formation is crucial not only for its development, but also for survival of microbial communities at colonized host sites (Schmidt et al, 2008) as well as on medical devices (Ramage et al, 2006). The two media tested, YNB and RPMI 1640, have remained favourite choices for in vitro biofilm formation (Biswas & Chaffin, 2005;Cateau et al, 2008;Chandra et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis (2-DE) of C. glabrata in response to changes in ambient pH (4.0, 7.4 or 8.0) [73] reveal a statistically significant change in protein expression level. Peptide mass fingerprinting identified proteins involved in glucose metabolism, the TCA cycle, respiration and protein synthesis to have decreased expression during growth at pH 7.4 and/or 4.0, whereas proteins involved in stress responses and protein catabolism were preferentially expressed under alkaline (pH 8.0) conditions.…”
Section: Stress Responses In Eukaryotic Microorganismsmentioning
confidence: 99%
“…Adaptation to and tolerance of bile stress are important limiting [73] Candida glabrata Different pH pH 7. factors to ensure survival of bifidobacteria in the intestinal environment of humans. The effect of bile salts on protein expression patterns of Bifidobacterium longum has been examined by using proteomic analyses [51] with the identification of 34 differentially regulated proteins, the majority of which were induced after both a minor (0.6 g/1) and a major (1.2 g/l) exposure to bile.…”
Section: Stress Responses In Prokaryotic Microorganismsmentioning
confidence: 99%